Potency evaluation of erythropoietin products: current status - L. A. Gaiderova; N. A. Alpatova; S. L. Lysikova; A. M. Guskov; O. V. Golovinskaya (Биопрепараты: Профилактика, диагностика, лечение)
INTRODUCTION. Given the widespread clinical use of recombinant human erythropoietin (rhEPO) products from different manufacturers, potency assays should ensure that patients receive comparable doses of rhEPO across medicinal products. The harmonisation of approaches to potency testing requires the use of pharmacopoeial bioassays and appropriate international/pharmacopoeial reference standards (RSs).AIM. This study aimed to summarise information on pharmacopoeial requirements, relevant RSs, and bioassays (in vivo and in vitro) for the assessment of rhEPO potency, as well as to analyse the pharmacopoeial compliance of manufacturers’ specifications for rhEPO products authorised in Russia.DISCUSSION. This article presents information on the molecular structure of erythropoietin. The glycosylation profile of erythropoietin not only accounts for most of the differences in the half-life and biodegradation rate but also significantly influences the potency of rhEPO products. The authors outlined the pharmacopoeial requirements for potency assays in vivo, summarised the information on RSs for potency determination, characterised the development of potency assays in vitro, and studied the possibility of including in vitro assays in pharmacopoeias. The analysis showed that some potency assays used for rhEPO products manufactured in Russia did not comply with the requirements of the State Pharmacopoeia of the Russian Federation.CONCLUSIONS. The study identified the need to develop and certify a national pharmacopoeial RS for the potency of rhEPO in order to satisfy the demands of Russian manufacturers in the context of import substitution. To implement adequate 3R-compliant methods for rhEPO quality assessment, it is necessary to harmonise approaches to potency testing of rhEPO products and develop a consolidated document governing such testing.